Job search, unemployment insurance, and active labor market policies - Thomas Le Barbanchon; Johannes Schmieder; Andrea Weber (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This chapter, prepared for the Handbook of Labor Economics, presents a comprehensive overview of how labor economists understand job search among the unemployed and how job search is shaped by unemployment insurance (UI) and active labor market policies (ALMP). It focuses on synthesizing key lessons from the empirical research of the last decade and presents recent novel theoretical developments.
Keywords: 330; job search; unemployment insurance; active labor market policies